Corruption and Economic Growth : Evidence from Southeast Asia Countries - Tiang, Jang Haw (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study examines the relationship between corruption and economic growth of the Association of Southeast Asian Nations (ASEAN) covering the period from 1996 to 2018. The pervasiveness of corruption and robust economic growth discover for most of ASEAN countries which opposed with the conventional propositions of detrimental effect of corruption on growth or development. Limited studies in this region unable to provide further empirical evidence to explain the discovered phenomena. Hence, the analysis is conducted based on the panel unit root test, panel cointegration test, panel Autoregressive Distributed Lag (ARDL) models, and panel causality test. The findings revealed there is significant U-shaped relationship between control of corruption and economic growth. The calculation of threshold of controlling corruption denotes ASEAN countries can achieve towards lower corruption levels and sustainable economic growth at the very beginning. The panel Granger causality test denotes causality between corruption and economic growth as well as other control variables are mutually complementary to one another.